Genetic ancestry and the colonial legacies of race in genomics: a cross-disciplinary dialogue - Schwartz-Marin, Ernesto; Jiwani, Tayyaba; Abel, Sarah; Egorova, Yulia; M’charek, Amade; Meyer, Diogo; Moreno Estrada, Andrés; Schramm, Katharina; Wade, Peter; Naslavsky, Michel (Frontiers in Genetics, 2025)
As genomics initiatives have spread around the world–often in the name of genetic diversity and inclusion–they have not only invoked promises of a medical revolution, but also revived categories of human difference that resemble erstwhile racial classifications. This is despite the fact that geneticists broadly dismissed racial categories as obsolete and unfounded after the Human Genome Project was completed in 2003. In fact, contemporary genomics initiatives have often ended up reinforcing ethnocentric and nativist conceptions of difference, drawing intense criticism from activists and critical social scientists. This roundtable brings leading population geneticists grappling with the question of genetic identity and ancestry, especially in the global South, together with some of the most prominent scholars of race in genomics. The result is an engaging and insightful dialogue on questions that have vexed the field for decades. How do we—indeed “can” we reconcile the boundaries of biological and social difference? How do notions of “genetic ancestry” and “biogeographical ancestry differ from erstwhile racial and ethnic categories? Can racial categories ever be shorn of their colonial and oppressive legacies? Here we scrutinise the methodological and epistemological frameworks in contemporary genomics that work to define populations and shape our understanding of biology, society, health, and disease. We seek to clarify perspectives across the disciplinary divide, and to advance constructive and grounded critiques that contend with the question of justice in genomics.